Perceived Social Support and Trait Emotional Intelligence in Adolescent Bullying Victims at School - Aathirah Aura Zahra; Maria Jane Tienoviani Simanjuntak (P3KM Politeknik Pertanian Negeri Samarinda, 2026)
Bullying is a serious problem in society. Victims who experience bullying will experience negative impacts. However, the presence of social support can help adolescents reduce the negative impacts received. This study aims to examine the effect of Perceived Social Support on Trait Emotional Intelligence in victims of bullying in adolescence. This study used the Children Bullying Scale (CABS) as a screening tool, Multidimensional Perceived Social Support (MSPSS) and Trait Emotional Intelligence (TEIQue-ASF). To test the results of this study, linear and descriptive regression tests were used. The study was administered to 112 respondents, male and female, who were active high school students. The results showed a significant influence between perceived social support and trait emotional intelligence. Social support from family can help individuals improve their perceived emotional intelligence. This research indicates higher the perceived social support for each individual, the higher the perceived level of emotional intelligence. This is related to self-esteem, self-confidence, and the individual's interactions with their surroundings.